Sex differences and impact of body mass on performance from childhood to senior athletes in Olympic weightlifting - Huebner, M.; Perperoglou, A. (PLOS ONE, 2020)
Background: Olympic weightlifting requires technical skills, explosive power, strength, and coordination. Weightlifters can be competitive within a range of morphological characteristics due to competition body weight classes. To date no studies have examined when sex differences arise in weightlifting and the impact of body mass on performances at different ages.